Lambent traces : Franz Kafka - Corngold, Stanley (Princeton University Press, 2004)
On the night of September 22, 1912, Franz Kafka wrote his story "The Judgment," which came out of him "like a regular birth." This act of creation struck him as an unmistakable sign of his literary destiny. Thereafter, the search of many of his characters for the Law, for a home, for artistic fulfillment can be understood as a figure for Kafka's own search to reproduce the ecstasy of a single night. In Lambent Traces: Franz Kafka, the preeminent American critic and translator of Franz Kafka traces the implications of Kafka's literary breakthrough. Kafka's first concern was not his responsibili.